Pivotal role for endothelial tetrahydrobiopterin in pulmonary hypertension. - Khoo, J; Zhao, L; Alp, N; Bendall, J; Nicoli, T; Rockett, K; Wilkins, MR; Channon, K (2005)
BACKGROUND: Pulmonary hypertension is a fatal disease characterized by vasoconstriction and vascular remodeling. Loss of endothelial nitric oxide bioavailability is implicated in pulmonary hypertension pathogenesis. Recent evidence suggests that the cofactor tetrahydrobiopterin (BH4) is an important regulator of nitric oxide synthase enzymatic function. METHODS AND RESULTS: In the hph-1 mouse with deficient BH4 biosynthesis, BH4 deficiency caused pulmonary hypertension, even in normoxic conditions, and greatly increased susceptibility to hypoxia-induced pulmonary hypertension. In contrast, augmented BH4 synthesis in the endothelium, by targeted transgenic overexpression of GTP-cyclohydrolase I (GCH), prevented hypoxia-induced pulmonary hypertension. Furthermore, specific augmentation of endothelial BH4 in hph-1 mice by crossing with GCH transgenic mice rescued pulmonary hypertension induced by systemic BH4 deficiency. Lung BH4 availability controlled pulmonary vascular tone, right ventricular hypertrophy, and vascular structural remodeling in a dose-dependent manner in both normoxia and hypoxia. Furthermore, BH4 availability had striking effects on the immediate vasoconstriction response to acute hypoxia. These effects of BH4 were mediated through the regulation of nitric oxide compared with superoxide synthesis by endothelial nitric oxide synthase. CONCLUSIONS: Endothelial BH4 availability is essential for maintaining pulmonary vascular homeostasis, is a critical mediator in the pathogenesis of pulmonary hypertension, and is a novel therapeutic target.